The Decapoda described by Henri Filhol: checklist and dates of publication (Crustacea: Anomura, Brachyura, Caridea) - Low, Martyn E. Y. (Zootaxa, 2013)
Henri Filhol authored thirteen publications that established new names for decapod crustaceans in 1884 and 1885. The accurate dates of these publications are determined utilising notices of Filhol’s publications in contemporary journals and library date-stamps. A checklist of the names for the Decapoda established by Filhol and their current identities is present-ed. Labophrys Filhol, 1885, and not Lobophrys, is shown to be the correct spelling for the junior objective synonym of Paramithrax H. Milne Edwards, 1834 (type species Pisa barbicornis Latreille, in Latreille, Le Peletier, Serville & Guérin, 1825) (Brachyura: Majidae Samouelle, 1819).